KOMUNIKASI ANTAR PRIBADI ORANGTUA DAN ANAK DALAM PROSES PENGEMBANGAN BAKAT DAN PEMILIYHAN KARIR ANAK DENGAN PILIHAN PROFESI MUSISI - Melinda Ayu Santosa; Agus Naryoso (Interaksi Online, 2019)
This study aims to understand the patterns of communication between parents and children in the process of developing talent and choosing a child's career with a choice of musician profession. The method used in this study is qualitative research with a phenomenological approach. The theories used in this study are Family Relations Schema Theory, Theory Self Disclosure and Emotional Intelligence Theory. In this study it was found that, to help children in developing talent and musical careers required high conversation orientation, supportive communication, and pluralistic types within the family. Suggestions that can be given are parents and children must increase the intensity of communication within the family to be able to creating openness and closeness to parent and child relationships and helping children achieve success.